Optimization of Stir-Squeeze Casting Parameters to Analyze the Mechanical Properties of Al7475/B4C/Al2O3/TiB2 Hybrid Composites by the Taguchi Method. (12th September 2022) - Gugulothu, Bhiksha; Anusha, P.; Swapna Sri, M. Naga; Vijayakumar, S.; Periyasamy, R.; Seetharaman, Suresh
Abstract : Stir-squeeze casting (SSC) is the appropriate and inexpensive technique for producing aluminum hybrid matrix composites as it creates a uniform distribution of reinforcements in the composite with finer grains. Al7475 is a lightweight castable alloy that possesses enough hardness and strength with applications in automotive and aerospace. This research work examines the effect of process parameters for Al7475/Al2 O3 /B4 C/TiB2 hybrid matrix composites produced by the stir-squeeze casting methodology. As per Taguchi design L16, four parameters with four levels were selected in the optimization process of SSC are stir speed (SD) of 300-450 rpm, melting temperature (ME) of 750–900°C, squeeze pressure (SE) of 50-125 MPa, and reinforcement (RT) of 2-8 wt%. The mechanical properties such as tensile strength (TS) and hardness (HN) are studied by the variation of each process parameters levels. The optimization results on TS and HN are predicted by Minitab-17 Software. It is observed that maximum TS of 325 MPa and HN of 130.6 Hv are attained at experiments L1 and L7, respectively. From the SN ratio result, the TS value is improved at the parameter level of RT2-SE4-ME2-SD4. The ANOVA result exposed that reinforcement is the most significant factor for enhancing tensile strength which contributes 38.9%, followed by squeeze pressure of 28.4%, stir speed of 13.6%, and melting temperature of 12.16%.